FAKTOR-FAKTOR YANG MEMPENGARUHI PERDAGANGAN LINTAS BATAS NEGARA INDONESIA-TIMOR LESTE - Syahid, Shasah Husani; Amtiran, Paulina Y; Makatita, Reyner F; Foenay, Christien C (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2023)
Cross-border trade is trade carried out between residents of two countries bordering certain values. One of the NTT areas which is directly adjacent to the country of Timor Leste is Belu Regency. The purpose of this study was to determine the factors that influence the occurrence of cross-border trade between Indonesia and Timor Leste. The method used in this research is qualitative with a descriptive approach. Data collection techniques namely Observation/Observation, Interview and FGD, and documentation. The data analysis technique used is descriptive qualitative. This study uses the Milles and Huberman analysis tools. The results show that natural resource, human resource, socio-cultural, and financial factors can influence trade across the Indonesia-Timor Leste border. Abundant natural resources in Belu Regency can encourage community economic growth. However, human resources in Belu Regency are still very low so that they have not been able to utilize the potential of existing natural resources which can be an obstacle to cross-border trade.